2020
DOI: 10.1016/j.jaut.2020.102523
|View full text |Cite
|
Sign up to set email alerts
|

Experience with tocilizumab in severe COVID-19 pneumonia after 80 days of follow-up: A retrospective cohort study

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 28 publications
(44 reference statements)
5
45
2
Order By: Relevance
“… 153 Moreno et al (2020) also found that TCZ decreased mortality and duration of hospital stay in critically ill patients but seemed to have a high risk of serious infections. 154 Similar outcomes were reported in another related study involving 158 COVID-19 patients. 155 Somers et al (2020) also found that tocilizumab significantly decreased mortality among 154 patients with severe COVID-19.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“… 153 Moreno et al (2020) also found that TCZ decreased mortality and duration of hospital stay in critically ill patients but seemed to have a high risk of serious infections. 154 Similar outcomes were reported in another related study involving 158 COVID-19 patients. 155 Somers et al (2020) also found that tocilizumab significantly decreased mortality among 154 patients with severe COVID-19.…”
Section: Resultssupporting
confidence: 81%
“… 165–170 In addition to a lack of effectiveness with TCZ, Moreno Perez et al (2020) also found that critically ill patients taking TCZ appeared to have a high risk of severe infections. 154 Consequently, despite the promise shown by tocilizumab in relieving inflammation, decreased mortality, and duration of hospital stay in some studies, we believe more research is needed before the place of TCZ in the treatment of patients with COVID-19 can be fully elucidated. 163 …”
Section: Resultsmentioning
confidence: 99%
“…Non-randomised studies have suggested that tocilizumab might have a role in controlling cytokine release syndrome associated with covid-19. 26 27 28 29 30 31 32 33 34 Most observational studies, although not all, suggest a benefit of tocilizumab on clinical outcomes. 26 30 31 33 Results from observational studies are, however, limited owing to a high risk of confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Intense exercise also produces large quantities of IL-6 [23] , which may account for the more severe clinical manifestations of infection amongst athletes [24] . Indeed, dexamethasone, which lowers production of IL-6 by human bronchial epithelium [25] , has recently been successfully trialled in COVID-19 patients [26] , and there is increasing evidence that tocilizumab, an IL-6 antagonist, can result in improved outcomes amongst severely affected patients [27] .
Fig.
…”
Section: Discussionmentioning
confidence: 99%